The comparative and functional cranial morphology of the early Therocephalia (Amniota: Therapsida) - Van den Heever, Jurgens Abraham (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Phil)—Stellenbosch University, 1987.